Hybrid PSOGSA Method of Solving ORPD Problem with Voltage Stability Constraint - J. Jithendranath; A.Srihari Babu; G.Durga Sukumar (Institute of Advanced Engineering and Science, 2014)
This paper presents a new hybrid evolutionary based algorithm based on PSO and GSA for solving optimal reactive power dispatch problem in power system. The problem was designed as a Multi-Objective case with loss minimization and voltage stability as objectives. Generator terminal voltages, tap setting of transformers and reactive power generation of capacitor banks were taken as optimization variables. Modal analysis method is adopted to assess the voltage stability of system. The above presented problem was solved on basis of efficient and reliable technique which takes the advantages of both PSO and GSA. The proposed method has been tested on IEEE 30 bus system where obtained results were found satisfactorily to a large extent that of reported earlier.